A New 35-mm Short Intra-aortic Balloon Catheter: A Suitable Option Also for Non–Small-Sized Patients?. Issue 1 (January 2016) - Gelsomino, Sandro; Lozekoot, Pieter Willem; Lorusso, Roberto; de Jong, Monique Maria; Parise, Orlando; Matteucci, Francesco; Lucà, Fabiana; Kumar, Narendra; Dehkord, Eshan Sadeghian; Romano, Salvatore Mario; Gensini, Gian Franco; La Meir, Mark; et al.
Abstract : Objective: Visceral ischemia can be a potentially life-threatening complication of intra-aortic balloon pump (IABP) support. A shorter IABP catheter might lead to a reduction of visceral complications. In this animal study, we evaluate the effects of a 35-mL short catheter in comparison with a 40-mL standard-sized catheter. Methods: Eighteen healthy swine underwent 120-minute ligation of the left anterior descending coronary artery followed by 6 hours of reperfusion being supported by either a short IABP catheter (short group) (n = 6) or a long IABP catheter (long group) (n = 6) or with no assistance (controls) (n = 6). Hemodynamics, visceral and coronary flows, as well as biochemical markers were evaluated throughout the different phases of the protocol. Results: Mesenteric flows increased significantly at reperfusion ( P < 0.001 both) remaining constant afterward (all, P > 0.05) in the short group, while remaining significantly lower in the long group at the start of reperfusion, remaining constantly lower than the short group and controls ( P < 0.001 vs short, P < 0.003 vs controls). In both long and short groups, catheters improved renal flows at reperfusion ( P < 0.001 both) without any further variation ( P > 0.05). In the short group, the flows were higher during the whole of reperfusion (all, P < 0.05). Intra-aortic balloon pump support improved hemodynamic indices and coronary blood flows during reperfusion to a similar extent in both the small and the long group ( P > 0.05). Conclusions: The short IABP catheter proved to be as effective as the standard-sized catheter in supporting hemodynamics and coronary circulation. Furthermore, it even improves visceral flows in comparison with conventional IABP catheters.